(untitled) (Interdisciplinary Studies Journal, 2024)
There is a demand for overcoming gender inequalities, and, in our specific case, different groups of women. Based on this, this article aims to present the results of an Extension Project, conducted at the Federal University of Amazonas. Project meetings were held with teachers, administrative workers and students from the Campus, in addition to the organization of a lecture on the topic for students and other members of the community in the municipality of Coari. The implementation of these activities sought to maintain the exchange of experiences in this academy/city relationship, promoting sisterhood and combating violence that persists in this state. Based on this experience, it is considered that there is resistance, in addition to the lack of knowledge on the subject, caused by the oppression of a sexist society in different spaces, resulting in gender oppression and prejudice surrounding Feminism.